2020
DOI: 10.18502/keg.v5i6.7039
|View full text |Cite
|
Sign up to set email alerts
|

Passengers Comfort Perception and Demands on Railway Vehicles: A Review

Abstract: Trains are becoming a popular way of transportation driven by comfort and ecology reasons. Latest statistics showed an increasing of 40% on the number of passengers in the last decade. The development of new high-speed trains promoted an evolution on the coaches interiors, as to make railway transportation more attractive. To cope this objective, new requirements were set, namely high levels of comfort and safety. In complement, multiple long-term ride comfort evaluation methods have been developed. The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The time history of the rail suspension response under sinusoidal track excitation is shown in Figs. (7)(8)(9)(10)(11); RVBA, RVBD, PSA, PSVD, and STD, respectively. Passive represents the vehicle model without an MR damper and depends on a conventional damper.…”
Section: Sinusoidal Track Profilementioning
confidence: 99%
See 2 more Smart Citations
“…The time history of the rail suspension response under sinusoidal track excitation is shown in Figs. (7)(8)(9)(10)(11); RVBA, RVBD, PSA, PSVD, and STD, respectively. Passive represents the vehicle model without an MR damper and depends on a conventional damper.…”
Section: Sinusoidal Track Profilementioning
confidence: 99%
“…Rail vehicles are the backbone of an integrated system because of their capacity and speed; they are becoming one of the most important and popular public transportation worldwide. Lately, statistics have reported that, in the past decade, the number of train passengers has increased by about 40% [10] Many researchers are motivated to minimize the vertical vibration transmitted to train passengers from rail irregularities to improve passenger comfort. The high levels of vibration annoy passengers and significantly affect human health due to the many hours spent riding trains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Passengers' travel comfort is associated with the departure time and degree of accessibility to trains [61]. Train comfort is defined by multiple factors such as vibration, noise, temperature, humidity, smell, visual stimulation, and design layout [62]. According to the respondents' comments in the questionnaire survey, train comfort includes the train's air conditioning system and information.…”
Section: ) Comfortmentioning
confidence: 99%
“…The comfort of taking high-speed rail is receiving a lot of attention from passengers; there has been rapid development of the high-speed rail industry and a sharp increase in the number of people who choose to travel by high-speed rail [ 1 , 2 , 3 ]. The change in the environment during the high-speed train driving is a critical ingredient that causes the temperature change in the high-speed train compartment, such as outside temperature, light intensity, speed, and other factors [ 4 ]. Because of its high hysteresis, the air conditioner’s air supply temperature will fluctuate with the temperature of the high-speed train compartment, causing human discomfort and making control difficult.…”
Section: Introductionmentioning
confidence: 99%